COMT Val158Met moderates the link between rank and aggression in a non‐human primate. (20th December 2017) - Gutleb, D. R.; Roos, C.; Noll, A.; Ostner, J.; Schülke, O.
Abstract : The COMT Val 158 Met polymorphism exists in a non‐human primate and moderates the link between rank and aggression. Abstract : The COMT Val 158 Met polymorphism is one of the most widely studied genetic polymorphisms in humans implicated in aggression and the moderation of stressful life event effects. We screened a wild primate population for polymorphisms at the COMT Val 158 Met site and phenotyped them for aggression to test whether the human polymorphism exists and is associated with variation in aggressive behavior. Subjects were all adults from 4 study groups (37 males, 40 females) of Assamese macaques ( Macaca assamensis ) in their natural habitat (Phu Khieo Wildlife Sanctuary, Thailand). We collected focal animal behavioral data (27 males, 36 females, 5964 focal hours) and fecal samples for non‐invasive DNA analysis. We identified the human COMT Val 158 Met polymorphism (14 Met/Met, 41 Val/Met and 22 Val/Val). Preliminary results suggest that COMT genotype and dominance rank interact to influence aggression rates. Aggression rates increased with rank in Val/Val, but decreased in Met/Met and Val/Met individuals, with no significant main effect of COMT genotype on aggression. Further support for the interaction effect comes from time series analyses revealing that when changing from lower to higher rank position Val/Val individuals decreased, whereas Met/Met individuals increased their aggression rate. Contradicting the interpretation of earlier studies, we show that the widely studied Val 158 Met polymorphism in COMT is not unique to humans and yields similar behavioral phenotypes in a non‐human primate. This study represents an important step towards understanding individual variation in aggression in a wild primate population and may inform human behavioral geneticists about the evolutionary roots of inter‐individual variation in aggression.